Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Kelurahan Harapan Jaya - Monica Sasqia Anwar; Supriyanto Supriyanto (Departement of Mathematics Education, 2023)
For organizations that can provide services, including such governm:ent agencies focused on providing community service, accessibility and services are essential. Employees at the Harapan Jaya Village Office functioned as the study's subject in this quantitative research. methods for collecting information using questionnaires. The study's results suggested that the variables